Apocynin ameliorates testicular toxicity in high-fat diet-fed rats by regulating oxidative stress - ERTAŞ, BÜŞRA; ERCAN, FERİHA (My University, 2023)
Objective: The purpose of this study was to examine the effects of apocynin (APC), an inhibitor of NADPH oxidase (NOX), on high-fat diet (HF)-induced testis cytotoxicity.Methods: Wistar albino rats were divided into three groups as control, HF and HF+APC groups. Rats in HF and HF+APC groups were fed using HFfor 16 weeks and in the last four weeks of this period vehicle solution or APC (25 mg/kg) was administered orally five days a week, respectively.Control group was fed with standart lab chow for 16 weeks. Cholesterol, triglyceride, high-density lipoproteins, leptin, estrogen, testosterone,LH and FSH were estimated in blood serum. Sperm parameters were analysed from the epididymis. Testicular malondialdehyde, 8‐hydroxy‐2‐deoxyguanosine, glutathione, superoxide dismutase and myeloperoxidase levels were estimated biochemically. Testicular morphology,proliferative, apoptotic and NOX2-positive cells were analysed histologically.Results: HF-induced obesity caused significant alterations in serum lipid and hormone profiles. Testicular malondialdehyde, 8‐hydroxy‐2‐deoxyguanosine, and myeloperoxidase levels increased, glutathione and superoxide dismutase levels decreased in this group. Moreover,altered sperm parameters, increased degenerated seminiferous tubules, apoptotic and NOX2 – positive cells and decreased proliferative cellswere observed in the HF group. All these biochemical and histological alterations improved in the HF+APC group.Conclusion: HF-induced obesity causes altreations in lipid values, sperm parameters and testicular morphology by increasing oxidative stressthrough NOX2 activity. Apocynin might prevent testis damage via regulating oxidant/antioxidant balance.
Keywords: Tıp; Histoloji-Embriyoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Histology and Embryology; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Moleküler Biyoloji ve Genetik; TIP, GENEL & DAHİLİ; HÜCRE BİYOLOJİSİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; MEDICINE, GENERAL & INTERNAL; CELL BIOLOGY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Hücre Biyolojisi; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Cell Biology; Life Sciences; High fat diet; apocynin; testis; apoptosis; oxidative stress